A randomized phase 3 trial of total neoadjuvant therapy (induction chemotherapy, neoadjuvant chemoradiation, neoadjuvant chemotherapy, and surgery) vs. standard long-term chemoradiation therapy (neoadjuvant chemoradiation, surgery, and adjuvant chemotherapy) in locally advanced rectal cancer - Foroughi, Freshte; Javadinia, Seyed Alireza; Salek, Roham (Frontiers in Oncology, 2024)
PurposeThe management of rectal adenocarcinoma has evolved during the last decade, shifting from a conventional neoadjuvant chemoradiotherapy, surgery, and adjuvant chemotherapy in all cases to a total neoadjuvant approach, especially in locally advanced tumors when a sphincter-sparing surgery has been planned. However, the exact indications and the neoadjuvant regimen with the highest response remain unresolved. We aimed to assess whether administering neoadjuvant chemotherapy before and after preoperative chemoradiotherapy could increase the pathological complete response (pCR) rates.MethodsWe conducted a phase 3, multicenter, randomized trial at four hospitals in Iran. Adult patients with a newly diagnosed, biopsy-proven, locally advanced non-metastatic rectal adenocarcinoma with an ECOG performance status of 0–2 were randomly assigned (2:2) to either the total neoadjuvant treatment (TNT) or the standard-of-care groups using a block randomized design. Investigators and participants were not masked to treatment allocation and groups. The TNT group received neoadjuvant chemotherapy with FOLFOX6 (intravenous 85 mg/m2 oxaliplatin and 400 mg/m2 leucovorin, followed by intravenous 400 mg/m2 fluorouracil bolus and then continuous infusion at a dose of 2,400 mg/m2 over 46 h every 14 days for four cycles before and four cycles after chemoradiotherapy), chemoradiotherapy (50.4 Gy during 28 fractions and 800 mg/m2 concurrent oral capecitabine twice daily 5 days per week), and total mesorectal excision. The standard-of-care group received neoadjuvant chemoradiotherapy, total mesorectal excision, and adjuvant chemotherapy (eight cycles). The primary endpoint was the pathological complete response. Safety analyses were conducted on treated patients.ResultsOverall, 25 and 27 patients were enrolled in the TNT and standard-of-care groups, respectively. Both groups were similar in terms of gender, age, and tumor differentiation. The tumors in the standard-of-care group were significantly located closer to the anal verge compared with those in the TNT group (9.4 ± 3.7 cm in TNT vs. 6.8 ± 4 cm in standard, p = 0.02). A pCR was reached in 48% (12/25) and 25.9% (7/27) of patients in the TNT and standard-of-care groups, respectively (p = 0.4). The R0 resection rates were identical between the two groups (92% vs. 88.9%, p = 0.3). Moreover, the toxicity rates were similar between the two groups.ConclusionOur results showed that TNT is a safe and feasible treatment approach in patients with rectal cancer and may improve the overall pCR rate compared with standard treatment.Clinical trial registrationhttps://irct.behdasht.gov.ir/trial/65666, identifier IRCT20220723055527N1.